Identification and Prevalence of Gastrointestinal Parasites in the Feces of Sapera Goats at Jawara Farm - Arif, Hafaz; Jasmi, Riski Andrian; Rachim, Dimas Kukuh Nur (Al-Hayat: Journal of Biology and Applied Biology, 2025)
Livestock health is a crucial factor that influences the success of animal farming. One of the determinants of livestock health is the presence of parasites. This study aims to identify the types of gastrointestinal parasites and determine their prevalence in Sapera goats at Jawara Farm. The research was conducted using three examination methods: native, sedimentation, and flotation. A total of 23 goat fecal samples were examined in the laboratory. The identification results revealed five types of gastrointestinal parasites: Haemonchus contortus, Trichuris spp., Eimeria hirci, Eimeria christenseni, and Eimeria aspheronica. The parasite with the highest prevalence was Haemonchus contortus (69%), followed by Trichuris spp. (39%), Eimeria aspheronica (26%), Eimeria hirci (17%), and Eimeria christenseni (13%). The highest average Egg Per Gram (EPG) was found in Trichuris spp. (379.17), categorized as a moderate infection. Environmental factors such as temperature, humidity, and pen hygiene are strongly suspected to influence the prevalence rate and severity of parasitic infections. This study is expected to serve as a foundation for efforts in controlling and preventing parasitic infections on farms.